2014
DOI: 10.1159/000369918
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bone Tissue Formation in a Flat Surface Attachment of a Bone Conduction Implant: A Pilot Study in a Sheep Model

Abstract: The bone conduction implant (BCI) is a new bone conduction hearing device implanted under intact skin. The transducer has a flat direct contact with the mastoid part of the temporal bone, and no screws are used. The sound signal is transmitted from the external audio processor to the implant by means of magnetic induction. In this study, osseointegration of a flat passive BCI transducer dummy in sheep skulls was assessed using quantitative and qualitative histology as well as cone beam computed tomography (CBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The transmission properties of this flat surface contact have been investigated in preclinical studies ( Håkansson et al, 2010 ; Taghavi et al, 2013 ), showing equally good transmission properties as a screw attachment of the transducer. The transducer-to-bone contact improved over time, and indicated stiffer and osseointegrated bone close to the implant, in a long-term study on sheep ( Taghavi et al, 2013 ; Eeg-Olofsson et al, 2014a ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The transmission properties of this flat surface contact have been investigated in preclinical studies ( Håkansson et al, 2010 ; Taghavi et al, 2013 ), showing equally good transmission properties as a screw attachment of the transducer. The transducer-to-bone contact improved over time, and indicated stiffer and osseointegrated bone close to the implant, in a long-term study on sheep ( Taghavi et al, 2013 ; Eeg-Olofsson et al, 2014a ).…”
Section: Discussionmentioning
confidence: 93%
“…The dura and the sigmoid sinus are in the majority of cases not encountered ( Reinfeldt et al, 2015a ). The BCI transducer is attached to the bone via a flat surface contact, and the transmission properties of this type of contact have been investigated in preclinical studies (H kansson et al, 2010; Taghavi et al, 2013 ; Eeg-Olofsson et al, 2014a ), showing equally good transmission as a screw attachment of the transducer. Moreover, the BCI surgery is considered safe and easy ( Eeg-Olofsson et al, 2014b ).…”
Section: Figurementioning
confidence: 99%
“…The clinical study on 20 patients is ongoing, and so far, six patients have received the implant. The audiometric results of the first patient at the 1-month follow-up are published by Eeg-Olofsson et al 49 and the first six patients’ 6-month follow-up by Reinfeldt et al 50 Before the clinical study, preclinical studies were performed on cadavers, 51 54 dry skulls, 55 animals, 56 , 57 and normal-hearing subjects. 58 In the important preclinical studies on the cadavers, 51 , 52 where it was first concluded that an active transcutaneous BCD could be a realistic alternative to a percutaneous system, the sound processor and induction link from the Vibrant Soundbridge (the study was supported by MED-EL) was used to drive a BEST transducer.…”
Section: Bone-conduction Devicesmentioning
confidence: 99%
“…This is one of the reasons that the BCI transducer is attached against the flat surface in a prepared bottom plane of the recess. It has been proven in an animal study that the transmission to the bone is equally good with a flat surface attachment as if it had been attached with a screw, 56 which is also seen by the bone contact underneath the transducer 57 (ie, the implant was found to be osseointegrated). The transducer protrudes 1–2 mm from the bone surface and is secured with a titanium wire over the casing, as described in Reinfeldt et al 50 It has been discussed whether it will be possible to just use compliant resorbable sutures instead.…”
Section: Trends In Developing Bcdsmentioning
confidence: 99%